Brexit and the Future of the Special Relationship between the United States and the United Kingdom - A. A. Aleshin; S. V. Kislitsyn (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The article examines the impact of Brexit on the special relationship between the United States and Great Britain. Throughout preceding decades, this relationship was marked by stability and unprecedented high level of political, military, economic and financial cooperation. On the basis of quantitative analysis of the U.S. and British databases of international treaties, the authors provide a comparative analysis of the dynamic of bilateral relationship between the two countries from 1940 to 2017, as well as of their relations with the leading European powers — France and Germany. The authors also examine a wide range of agreements which laid a formal basis for the special relationship in such spheres as military and technical cooperation as a whole and nuclear cooperation in particular, intelligence, trade, taxation, scientific and industrial cooperation. It is concluded that this extensive treaty framework renders bilateral relations more coherent and stable, but at the same time it reveals their asymmetric nature which made the United Kingdom follow the U.S. foreign policy strategy. However, the analysis of bilateral relations in the context of the British withdrawal from the EU allowed the authors to shed a new light on the essence and the prospects for the special relationship. The authors conclude that, in the medium-term, military and economic cooperation will continue since it is based on the objective interests of both sides. The U.S. needs British military bases and investment while the UK needs American technologies, especially in the nuclear sphere, and investment alike. Simultaneously, one cannot exclude changes in the longer term. The United States as the leader of the Western world expect Great Britain not only to follow its policy but to support it, i.a. by maintaining a high level of military spending. In turn, the UK new foreign policy, articulated in Global Britain strategy, may come into conflict with the U.S. interests while lack of military spending can diminish the UK role in ensuring transatlantic security. This may have a negative impact on the bilateral dialogue.